A Mechanical Theory to Account for Bitemporal Hemianopia From Chiasmal Compression - McIlwaine, Gawn G.; Carrim, Zia I.; Lueck, Christian J.; Chrisp, T. Malcolm (Journal of neuro-ophthalmology, 2005)
The association between bitemporal hemianopia and chiasmal compression is well recognized. The majority of chiasmal syndromes are caused by extrinsic compression from pituitary tumors, suprasellar meningiomas, craniopharyngiomas, and aneurysms. However, it is not clear why compressive lesions of the chiasm show a predilection for damage to nasal fibers with bitemporal hemianopia. Few experimental attempts at elucidating these mysteries have been reported and none has provided an adequate explanation. The authors postulate that the susceptibility of nasal fibers to preferential damage is explained by structural collapse theories as applied to crossing and noncrossing cylinders. By constructing a simplified mathematical model, the authors demonstrate that nasal fibers are subject to relatively greater pressures for any given external compressive force acting on the chiasm.